Phosphodiesterase type 5 inhibitors and erectile dysfunction - Catherine Whittaker (South African Family Practice)
Erectile dysfunction (ED) affects millions of men globally and may adversely affect his, and potentially his partners’, quality of life. The introduction, a decade ago, of the phosphodiesterase type 5- (PDE5-) inhibitors has revolutionised the management of ED. The PDE5-inhibitors have provided an effective and patient-acceptable therapy for ED. They have had a huge impact on public awareness and understanding of this disease. This article provides an overview of erectile dysfunction and the pharmacology, efficacy, safety and optimal use of the PDE5-inhibitors.